RabGAPs in skeletal muscle function and exercise. (January 2020) - Espelage, Lena; Al-Hasani, Hadi; Chadt, Alexandra
Abstract : The two closely related RabGAPs TBC1D1 and TBC1D4 are key signaling factors of skeletal muscle substrate utilization. In mice, deficiency in both RabGAPs leads to reduced skeletal muscle glucose transport in response to insulin and lower GLUT4 abundance. Conversely, Tbc1d1 and Tbc1d4 deficiency results in enhanced lipid use as fuel in skeletal muscle, through yet unknown mechanisms. In humans, variants in TBC1D1 and TBC1D4 are linked to obesity, insulin resistance and type 2 diabetes. While the specific function in metabolism of each of the two RabGAPs remains to be determined, TBC1D1 emerges to be controlling exercise endurance and physical capacity, whereas TBC1D4 may rather be responsible for maintaining muscle insulin sensitivity, muscle contraction, and exercise. There is growing evidence that TBC1D1 also plays an important role in skeletal muscle development, since it has been found to be associated to meat production traits in several livestock species. In addition, TBC1D1 protein abundance in skeletal muscle is regulated by both, insulin receptor and insulin-like growth factor-1 (IGF-1) receptor signaling. This review focuses on the specific roles of the two key signaling factors TBC1D1 and TBC1D4 in skeletal muscle metabolism, development and exercise physiology.